The Role of Stock Options in the Financial Sector and the Financial Crisis - Hewson, T (2009)
During the bull years leading up to the financial crisis, many fund managers and bankers believed that structured finance was revolutionary financial technology for transforming poor quality loans into high quality investments. Many had not accounted for the potential downside possibilities of these risky bets; increasing leverage, level of investment in risky assets and aggressiveness of debt policies, in attempts to increase overall stock price volatility. Moreover, the absence of deferred compensation institutionalized short-termism within the sector. Once interest rates started to rise and house prices started to fall, the whole edifice began to fall in on itself. These effects made the valuation of assets extremely uncertain and contributed to the rapid evaporation of secondary market liquidity and the subsequent failures of many leading global commercial and investment banks. Since the collapse of Lehman Brothers governments have spent or pledged at least $6 trillion to fight the crisis. The Lehman collapse shattered assumptions that were built up over decades; that modern finance eliminated risk., that asset prices would only rise and the market operates best when left alone. In this study I look at the role of stock options in promoting risk behaviours within the financial sector and these subsequent effects on the financial crisis. I find that CEOs who were are paid heavily with stock options generated extreme performance due to increased propensity to make large and high-variance bets; bets which contributed significantly to the crisis.